A computational study on reduction of aerodynamic heating and drag over a blunt body in hypersonic turbulent flow using counter flow jet. (24th September 2012) - Aruna, S.; Anjali Devi, S.P.
In hypersonic flights, two vital problems are drag and aerodynamic heating. Both problems can be palliated by modifying the flow field at nose region of the hypersonic blunt body by using jet. In this study, feasibility of utilising a counter flow jet for the reduction of total drag and aerodynamic heating around coneogive blunt body in hypersonic turbulent flow is investigated. Flow field around the blunt body is calculated numerically in the free stream of Mach number of 6.5. Computation of drag and aerodynamic heating is made in the absence of jet and in the presence of jet. Contours of Mach number, temperature and density are presented to describe the flow patterns. Effective jet conditions for reduction of drag and aerodynamic heating are obtained. Eventually, a code is developed based on adaptive neuro-fuzzy inference system (ANFIS) for validating the numerical results obtained through CFD software.